Analysis of oil palm land characteristics in Muting District, Merauke Regency, South Papua Province - Diapari Siregar; Ratna Mauli Lubis; Benny Hidayat (Indonesian Journal of Agricultural Research, 2026)
The growth and productivity of oil palm are strongly influenced by land characteristics. Merauke Regency, particularly Muting District, South Papua Province, has extensive land potential for oil palm development but requires a detailed evaluation of land suitability. This study aimed to analyze field land characteristics to determine land suitability classes for oil palm plantations. Field surveys and laboratory analyses were conducted in October 2022, using secondary climate data, direct soil morphological observations, and soil physical–chemical analyses. The parameters evaluated included rainfall and the number of rainy days over the past five years, as well as soil physical and chemical properties, and soil morphological characteristics. The results indicate that the study area is classified as Type-B climate according to the Schmidt and Ferguson (1951) classification. The dominant soil type is Acrustoxic Kanhaplustults, characterized by clay-dominated texture and generally low to very low chemical fertility status. These soil conditions suggest inherent limitations for optimal oil palm growth. Based on the land suitability evaluation following the criteria of the Palm Oil Research Center, the study area is classified as S3 (marginally suitable) for both actual and potential suitability classes. Light-limiting factors include rainfall, soil texture, and drainage, while moderate-limiting factors consist of dry months, effective soil depth, and soil pH. These constraints indicate the need for appropriate land management and soil improvement strategies to enhance productivity. Overall, this study provides essential baseline information for sustainable land development planning for oil palm plantations in Muting District, Merauke Regency.